The presence of truth in thought and practice - Bettineschi, Paolo (Razón y fe, 2025)
In this article, we discuss the presence of truth within human thought, through a theoretical and critical comparison with hermeneutics, analytical philosophy and neo-idealism. The thesis that is supported is that of pure realism, according to which truth is not foreign to human thought, but it is not a product of such thought either. The practical implications that derive from this position are extremely relevant: human practice asks and demands to operate with the truth or on the basis of the truth, especially with reference to the most important things. But human practice always develops in thought and on the basis of it. Therefore, if human thought were not capable of knowing the truth, all our practical actions would lose their meaning, their importance and their dignity.